Exploring the Reasons for the Migration of Iranian Elite Athletes: A Thematic Analysis - َAkbar Jaberi; Saeid Bahiraei; Saleh Afrasiabi (Archives in Sport Management and Leadership)
The purpose of this study was to explore the reasons for the migration of Iranian elite athletes. This research was a qualitative exploratory study that has been done using a thematic analysis. The research population included faculty members, senior managers and professional athletes familiar with the research topic. According to the research nature, 16 participants were interviewed through purposive sampling until reaching the theoretical saturation. The tool used in the research was a semi-structured interview. The thematic analysis of the data by Braun and Clarke’s (2006) method led to the extraction of 66 codes, 13 sub-themes and four main themes. The findings revealed that "Financial motivations", "Professional motivations", "Limitations", and "Supports" are the significant reasons for the migration of Iranian elite athletes. According to the research findings on the reasons for athlete migration demonstrated that the motives and reasons are highly diverse and multifaceted. Therefore, managing migration issues requires a multidimensional approach at national level.